Fear of Covid-19 Related Factors among Females in Indonesia: An Online Survey - Roxsana Devi Tumanggor; Intan Imaroh; Andrew Cashin (Faculty of Nursing Universitas Padjadjaran, 2021)
Background: The COVID-19 pandemic is a highly infectious flu outbreak which spread rapidly around the world. COVID-19 outbreak caused panic and is predicted to increase the prevalence of mental illnesses such as depression and anxiety disorder . Along with increased anxiety and decreased mood, increased fear has been detected. Purpose: To analyze the fear of COVID-19 related factors and measure the level of fear among women in Indonesia. Methods: This is a cross-sectional study with 242 women who was implemented using the fear of COVID-19 instrument. A convenience sample was utilized and was recruited via an online WhatsApp through personal text to the potential respondents. The respondents stated their agreement to participate on the Google form before proceeding to fill in the data and answer the instrument items. The analysis was carried out to obtain the frequency distribution, mean and P-value. The mean score of each instrument item and the overall items were calculated and compared based on demographic data using t-test for two variables and analysis of variance (ANOVA) for three or more variables. Furthermore, the scores obtained were categorized into low and high fear levels based on the overall mean, where scores from 0-17 were categorized as low-level fear and 18-35 as high-level fear. Results: The results showed that 90.9% of the respondents were within the age range of 15–25 years, with the majority being students. Based on the results of statistical tests, it was discovered that question 3 (Q3) and question 4 (Q4) were the two items that affected the level of women’s fear to COVID-19. Furthermore, the results of statistical tests using ANOVA showed that occupation (P-Value of 0.01) and age (P-Value of 0.004) has a significant effect on the fear of COVID-19. In addition, based on the overall score calculation showed that 72.3% samples have high-level fear and 27.7% has low-level fear. Based on the results of this study, it was discovered that women’s age and occupation influence the level of fear to COVID-19. Conclusion: This study highlighted the significance of pandemic related fear and can inform the development of future women’s health studies.